2022
DOI: 10.3389/fimmu.2022.941742
|View full text |Cite
|
Sign up to set email alerts
|

Complement and endothelial cell activation in COVID-19 patients compared to controls with suspected SARS-CoV-2 infection: A prospective cohort study

Abstract: BackgroundThromboinflammation may influence disease outcome in COVID-19. We aimed to evaluate complement and endothelial cell activation in patients with confirmed COVID-19 compared to controls with clinically suspected but excluded SARS-CoV-2 infection.MethodsIn a prospective, observational, single-center study, patients presenting with clinically suspected COVID-19 were recruited in the emergency department. Blood samples on presentation were obtained for analysis of C5a, sC5b-9, E-selectin, Galectin-3, ICAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…Amidst all, many protein changes in ECFCs+Crit cells were linked to CVDs, including cardiomyopathy (also seen in ECFCs+PCR cells), ventricular dysfunction, vaso-occlusion and thrombosis, ischemic stroke or even kidney thrombosis. In agreement with these results, functional assays reported that the levels of VCAM1 were up-regulated in response to all positive serums, as already seen in COVID-19 patients [73][74][75], while the angiogenic potential of ECFCs was impaired. Both situations are indicative of endothelial dysfunction associated with cardiovascular events [33,75].…”
Section: Discussionsupporting
confidence: 88%
“…Amidst all, many protein changes in ECFCs+Crit cells were linked to CVDs, including cardiomyopathy (also seen in ECFCs+PCR cells), ventricular dysfunction, vaso-occlusion and thrombosis, ischemic stroke or even kidney thrombosis. In agreement with these results, functional assays reported that the levels of VCAM1 were up-regulated in response to all positive serums, as already seen in COVID-19 patients [73][74][75], while the angiogenic potential of ECFCs was impaired. Both situations are indicative of endothelial dysfunction associated with cardiovascular events [33,75].…”
Section: Discussionsupporting
confidence: 88%
“…However, it is worth noting that three reports are currently contrasting with this trend. For instance, Bruni et al (29) stated that COVID-19 patients had insignificant levels of Gal-3 compared to controls. In line with this, Kusnierz-Cabala et al (34) reported no significant difference in serum Gal-3 levels in COVID-19 patients compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates, 524 records were screened by titles and abstracts. Following this step, 63 studies were evaluated by full texts, resulting in 18 final included studies (7,(19)(20)(21)(22)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). The PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) flow chart summarizing the selection process is available in Figure 1.…”
Section: Literature Search and Baseline Characteristics Of Included S...mentioning
confidence: 99%
“…ICAM-1 and VCAM-1 are cell adhesion molecules that mediate leukocyte-endothelial cell interactions and are expressed on injured lung and kidney tissues in COVID-19 and other forms of acute illness (37)(38)(39)(40)(41). They have also been linked to mortality in these settings, but their relationship to AKI is inconsistent (12,(42)(43)(44). sPDL-1 is the soluble form of a checkpoint molecule whose role in respiratory illness is not well-established.…”
Section: Discussionmentioning
confidence: 99%